Quality Evaluation of Vacuum Microwave‐Dried Immature Vegetable Soybean (Glycine Max [L.] Merr.). Issue 5 (17th July 2015) - Song, J.F.; Liu, C.Q.; Jiang, X.Q.; Li, D.J.
Abstract The main physiochemical indices related to evaluating the quality of vacuum microwave‐dried immature vegetable soybean were investigated by a combination of correlation analysis and principle component analysis (PCA). The results showed that in the 2.94–7.71% range, the moisture content of dried products was significantly related to L* and had a positive correlation with a* the rehydration ratio was significantly related to a* and had a positive correlation with b*, and L* was related to a* and had a positive correlation with total soluble solids (TSS). Six principal components could reflect most details with a cumulative contribution rate of 87.11%, where a*, rehydration ratio, TSS, yield, moisture content, hardness, fracturability and vitamin C content were the key factors. Through a comprehensive evaluation, Sudou No. 4, Sudou No. 8, Tongdou No. 5, Huaidou No. 8 and Xudou No. 17 were selected as the appropriate varieties for dry processing. The PCA model established was highly consistent with the results of sensory evaluation. Practical Applications Beyond different drying methods, particular varieties have important impacts on the quality of dried products. This work evaluates the quality of different varieties of vacuum microwave‐dried immature vegetable soybean with principle component analysis, elucidates the main physiochemical factors affecting the quality of dried products and constructs the evaluation model. As a consequence, this work will provide information relevant to the selection of dried products for maintaining good soybean processing quality.